Between Eden and Armageddon : the future of world religions, violence and peacemaking - Gopin, Marc (Oxford University Press, 2002)
This work represents an innovative attempt to integrate the study of religion with the study of conflict resolution. Marc Gopin argues that religion can play a critical role in constructing a global community of shared moral commitments and vision - a community that can limit conflict to its non-violent, constructive variety.